2013
DOI: 10.1029/gm095p0001
|View full text |Cite
|
Sign up to set email alerts
|

Live107Pd in the Early Solar System and Implications for Planetary Evolution

Abstract: We present a report on the status of 107 Pd (>r = 9.4 x 10 6 y) in the early solar system and the implications of its presence for protoplanet evolution. Over the last two decades we have carried out an extensive search for the evidence of presently extinct 107 Pd in meteorites. From these results we conclude that: 1) 107 Ag* (excess 107 Ag) is present in a wide variety of iron and stony-iron meteorites; 2) 107 Ag* is due to the in situ decay of 107 Pd in these meteorites; 3) Pd-Ag metal-PeS and metal whole-ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…Although most of the IVBs analyzed for Pd-Ag isotope systematics exhibit radiogenic Ag isotope compositions, they all plot below but approximately parallel to the Pd-Ag isochron of the IVA iron Gibeon (Chen and Wasserburg, 1996). This is surprising, because it would indicate a less radiogenic initial 107 Ag/ 109 Ag for the IVBs, in spite of their more volatile-depleted composition compared to IVA iron meteorites.…”
Section: Application To Ivb Iron Meteoritesmentioning
confidence: 78%
See 2 more Smart Citations
“…Although most of the IVBs analyzed for Pd-Ag isotope systematics exhibit radiogenic Ag isotope compositions, they all plot below but approximately parallel to the Pd-Ag isochron of the IVA iron Gibeon (Chen and Wasserburg, 1996). This is surprising, because it would indicate a less radiogenic initial 107 Ag/ 109 Ag for the IVBs, in spite of their more volatile-depleted composition compared to IVA iron meteorites.…”
Section: Application To Ivb Iron Meteoritesmentioning
confidence: 78%
“…For instance, different metal samples of the IVA iron meteorite Gibeon define an isochron corresponding to an initial 107 Pd/ 108 Pd of (2.40 ± 0.05) Â 10 À5 at the time of Pd-Ag closure, the highest and most precise ratio determined so far (Chen and Wasserburg, 1990). A detailed Pd-Ag study on a large set of magmatic iron meteorites has demonstrated the presence of excess 107 Ag in almost all investigated magmatic iron meteorites, with inferred initial 107 Pd/ 108 Pd ratios of between $1.5 Â 10 À5 and $2.5 Â 10 À5 (Chen and Wasserburg, 1996).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Extrapolation back to the time of CAI formation would yield an initial 107 Pd/ 108 Pd of approximately twice this value for the solar system, though with considerable uncertainty. Further isochrons were determined in many other iron and stony-iron meteorites, showing that there is a wide range of initial 107 Pd/ 108 Pd ratios, but that many samples have ratios in the range (1.5-2.5) Â 10 À5 (Chen and Wasserburg, 1996;Chen et al, 2002). There are a few iron meteorites and pallasites for which 107 Pd-107 Ag systematics have been studied and the 53 Mn-53 Cr systematics have been determined in phosphate inclusions (Chen and Wasserburg, 1996).…”
Section: Palladium-107mentioning
confidence: 99%
“…Further isochrons were determined in many other iron and stony-iron meteorites, showing that there is a wide range of initial 107 Pd/ 108 Pd ratios, but that many samples have ratios in the range (1.5-2.5) Â 10 À5 (Chen and Wasserburg, 1996;Chen et al, 2002). There are a few iron meteorites and pallasites for which 107 Pd-107 Ag systematics have been studied and the 53 Mn-53 Cr systematics have been determined in phosphate inclusions (Chen and Wasserburg, 1996). Some are clearly disturbed, but extrapolation of the line through four iron meteorites to the early solar system 53 Mn/ 55 Mn ratio of $ 6.7 Â 10 À6 implies an early solar system 107 Pd/ 108 Pd ratio of $ 5 Â 10 À6 .…”
Section: Palladium-107mentioning
confidence: 99%